2015
DOI: 10.1016/j.virol.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 Tax protein recruitment into IKKε and TBK1 kinase complexes enhances IFN-I expression

Abstract: The Tax protein expressed by human T-cell leukemia virus type 1 (HTLV-1) plays a pivotal role in the deregulation of cellular pathways involved in the immune response, inflammation, cell survival, and cancer. Many of these effects derive from Tax multiple interactions with host factors, including the subunits of the IKK-complex that are required for NF-κB activation. IKKɛ and TBK1 are two IKK-related kinases that allow the phosphorylation of interferon regulatory factors that trigger IFN type I gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 79 publications
0
19
3
Order By: Relevance
“…Our work directly contradicts two previous reports that claimed the activation of TBK1, IRF3, and IFN production by Tax (36,37). Our findings that IFN-␤ induction was compromised in HTLV-1-infected cells did not support the claim for activation of IFN induction.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our work directly contradicts two previous reports that claimed the activation of TBK1, IRF3, and IFN production by Tax (36,37). Our findings that IFN-␤ induction was compromised in HTLV-1-infected cells did not support the claim for activation of IFN induction.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings that IFN-␤ induction was compromised in HTLV-1-infected cells did not support the claim for activation of IFN induction. Although the interaction of Tax with TBK1 was shown in our work and another recent study (37), the functional consequence reported in these two studies was completely opposite. Our finding on Tax inhibition of TBK1 activity was supported by a cluster of evidence obtained from different cells and using different experimental approaches.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…A recent report shows that Tax interacts with TBK1/IKKε in transfected HEK293 cells (20). Consistent with this finding, we found that Tax was co-precipitated with IKKε (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In line with their high functional domain homology, Tax-1 and Tax-2 show interesting similarities in their ability to form complexes with cytoplasmic factors. We demonstrated that both Tax-1 and Tax-2 form complexes with NF-κB pathway components NEMO and p65/RelA, the scaffold protein TAB2, and IKKε and TBK1, two IKK-related kinases that participate in both the NF-κB pathway and signaling pathways mediated by interferon regulatory factors (IRF) [103,104]. We propose that Tax-1 and Tax-2 may be recruited into the TBK1/IKK complexes as scaffolding-adaptor proteins and thereby enhance expression of IFN-inducible genes [104].…”
Section: Tax-mediated Nf-κb Activationmentioning
confidence: 99%